The Effect Of The Drill Method On Basketball Shooting Skills In Extracurricular Students At SMA 5 Kota Bengkulu - Dede Kusmadi; Lina Try Astuty B.S; Martiani Martiani (Journal of Multidisciplinary Research, 2026)
This study aims to The Effect of Basketball Games on Shooting Skills of Extracurricular Players at SMA 5 Bengkulu City with This type of research is experimental research with a sample of players. The results of the study show that the drill method has a significant effect on improving basketball shooting skills in extracurricular students at SMA 5 Bengkulu City, showing that the t count value (3.57) > t table value (1.042). With the three tests in this study, namely the normality test, the homogeneity test and the hypothesis test with the results of the normality test showing that the test results for the Pre-Test data of the drill method group are Lh 0.160 and Ltable 0.190 with α = 0.05, it can be concluded that the data is normally distributed. The test results for the Post-Test data of the drill method group are Lh 0.135 and Ltable 0.190 with α = 0.05, so it can be concluded that the data is normally distributed, the homogeneity test is based on the criteria if Fcount (Fh) is smaller than Ftable (Ft) then in this research Fcount (Fh) 0.70 <1.43 Ftable (Ft) means that the population data is homogeneous.